Reverse Phase -High Performance Liquid Chromatography technique with Ultra-Violet detector for the Determination of Tenoxicam and Ibuprofen Drugs in the pure and Pharmaceutical tablets (Baghdad Science Journal, 2024)
Reversed-phase high-performance liquid chromatography (RP-HPLC) equipped with an ultraviolet (UV) detector is capable of detecting drugs in trace amounts. In this study, a simple and rapid method for quantifying tenoxicam (TNX) and ibuprofen (IBU) in pure and pharmaceutical samples was developed and validated. The target analytes assessed in the present study were separated with a C18 column (HPLC column, 5 µm, 150 × 4.6 mm). Acetonitrile and acidified water [0.7 mL of phosphoric acid (H3PO4) in 1000 mL water at 50/50%] were employed as the mobile phase at a 1 ml/min flow rate and a 20 µl sample injection volume at 25°C. Condition calibration curves for each drug were obtained within the 10–50 µg/mL dynamic concentration range. The method proposed in this study exhibited good performance, where the TNX and IBU recorded limit of detection (LOD) values of 1.5677 and 0.7911 µg/mL at 0.5, 1.3, 5.0, 7.0, 9.0, and 10.0 µg/mL. Resultantly, the method possessed specificity, linearity, precision, and accuracy. The suggested approach was satisfactory and appropriate for determining TNX and IBU levels during routine quality control assessments of medications in pure forms, mixtures, and formulations